PTN−PTPRZ signalling is involved in deer antler stem cell regulation during tissue regeneration. Issue 5 (28th October 2020) - Dong, Zhen; Li, Chunyi; Coates, Dawn
Abstract: A growing deer antler contains a stem cell niche that can drive endochondral bone regeneration at up to 2 cm/day. Pleiotrophin (PTN), as a multifunctional growth factor, is found highly expressed at the messenger RNA level within the active antler stem cell tissues. This study aims to map the expression patterns of PTN protein and its receptors in a growing antler and investigate the effects of PTN on antler stem cells in vitro. Immunohistochemistry was employed to localise PTN/midkine (MDK) and their functional receptors, protein tyrosine phosphatase receptor type Z (PTPRZ), anaplastic lymphoma kinase (ALK), NOTCH2, and integrin αV β3, on serial slides of the antler growth centre. PTN was found to be the dominantly expressed growth factor in the PTN/MDK family. High expression of PTPRZ and ALK co‐localised with PTN was found suggesting a potential interaction. The high levels of PTN and PTPRZ reflected the antler stem cell activation status during the regenerative process. When antler stem cells were cultured in vitro under the normoxic condition, no PTN protein was detected and exogenous PTN did not induce differentiation or proliferation but rather stem cell maintenance. Collectively, the antler stem cell niche appears to upregulate PTN and PTPRZ in vivo,  and PTN−PTPRZ signalling may be involved in regulating antler stem cell behaviour during rapid antler regeneration. Abstract : The active stem cell niche of antler growth centre appears to upregulate pleiotrophin (PTN) and protein tyrosine phosphatase receptor type Z (PTPRZ) in vivo. PTN−PTPRZ signalling may be involved in stem cell regulation during rapid antler regeneration.